AKAR PENDIDIKAN KEWARGANEGARAAN DI PESANTREN - Ahmad Baso (Jurnal Pendidikan Islam, 2012)
This paper aims to describe the other side of the Pesantren that has been stereotyped as a conservative, traditional, and old fashioned islamic education institution. The research used the historical method. Particularly, it attempted to analyze and interprete as well as crosscheck between the primary pesantren texts gained from bookstore flea market and the writings of Orientalists‘ displayed in the bookstore in Supermall which is always regarded to be more valid by the researchers of Islamic education. The findings showed that in pesantren, students were taught to be democratic, tolerant to others, respect differences (pluralism), and cosmopolitan to science. Moreover, those attitudes proved to be a fundamental ideology of our nation. In other words, understanding Pesantren actually understands how to love the nation and the State of Indonesia. Thus, education in pesantren refers to education of Islamic boarding schools intended to inculcate and love their own people.